Religious Education of Young Children and Teenagers during the Interwar Period as the Source of Humanization of Social Life - Aldona Zakrzewska (Nicolaus Copernicus University in Toruń, 2012)
There is no doubt that the Catholic doctrine played an important role in the educational reality of the interwar period and it was considered a vital element in the reconstruction of social order and the humanization of mass culture. Was it truly the source of humanization of social life in the Second Republic of Poland? The above question is the main presumption in this research. The undertaken analysis is outlined by two main assumptions. Firstly, it presents the social value of the process of education and religious instruction in beliefs of contemporary promoters of religious education. Secondly, it discusses various forms of religious education (catholic schools activities, the presence of religious education and practices in the national curriculum, functioning of religious youth school organisations) and their influence on young children and teenagers. Finally, it attempts to find out if the process of religious education benefited the social life with reference to the engrossing conflict between the Catholic Church and the state government in the interwar period over the methods of religious education.